STRATEGI PEMASARAN KOPI DI DESA BATU ROTOK KECAMATAN BATU LANTEH TAHUN 2020 - Novi Kadewi Sumbawati; Abdul Rahim; J Jumiati; Rosyidah Rachman (Fakultas Ekonomi dan Manajemen, 2021)
The purpose of this study was to know the marketing strategy of coffee in Batu Rotok Village, Batu Lanteh Sub-District in 2020. Type of this study was descriptive. Type of data used in this study was qualitative data in the form of informants' answers obtained directly through interviews. The informants of this study were coffee farmers in Batu Rotok Village, Batu Lanteh District. The data that had been collected were analyzed using the SWOT analysis technique. Based on the results of study showed that the internal factors that become strength of the coffee products produced in Batu Rotok Village was superior quality compared to other regional production, but the weakness was that production activities to marketing were still done traditionally. Meanwhile, the external factor that becomes an opportunity for coffee production in Batu Rotok Village was that the demand for coffee was still increase along with the increasing number of coffee connoisseurs, but the threat was that more and more modern companies were emerging which become competitors in marketing the coffee products. The strategy that can be used was to improve the quality and image of products that are well known to the public and expand market reach by utilizing various social media for marketing activities.